It won´t hurt a bit: Psychological comfort and clients’ loyalty to dental services - Lins, Cláudio de Luna; Troccoli, Irene Raguenet; Altaf, Joyce Gonçalves (Organizações & Sociedade, 2013)
Using a qualitative approach, this paper aims at identifying the importance that patients of dental services apply to the psychological comfort when considering new purchases of this service. The results show that patients rank as high the importance of psychological comfort when considering new purchases this service, based on various factors that they reported as relevant in order to feel psychologically comfortable and, consequently, confident in their dentists.